TNBC-derived Gal3BP/Gal3 complex induces immunosuppression through CD45 receptor - Annat Raiter; Julia Lipovetsky; Asaf Stenbac; Ido Lubin; Rinat Yerushalmi (OncoImmunology)
A preliminary study investigating immunotherapy strategies for aggressive triple negative breast cancer (TNBC) revealed an overexpression of genes involved in the release of extracellular vesicles (EVs). Proteins expressed by EVs play a role in reprogramming the tumor microenvironment and impeding effective responses to immunotherapy. Galectin 3 (Gal3), found in the extracellular space of breast cancer cells, downregulates T-cell receptor expression. Gal3 binds to several receptors, including CD45, which is required for T-cell receptor activation. Previously, we reported a novel tumor escape mechanism, whereby TNBC cells suppress immune cells through CD45 intracellular signals. The objective of this study was to determine the potential association of Gal3 with TNBC-secreted EVs induction of immunosuppression via the CD45 signaling pathway. EVs were isolated from MDA-MB-231 cells and the plasma of patients with TNBC. Mass spectrometry revealed the presence of Gal3 binding protein (Gal3BP) in the isolated small EVs, which interacted with TNBC secreted Gal3. Gal3BP and Gal3 form a complex that induces a significant increase in T-regulatory cells in peripheral blood mononuclear cells (PBMCs). This increase correlates with a significant increase in suppressive interleukins 10 and 35. Blocking the CD45 receptor in PBMCs cultured with tumor-derived EVs impeded the immunosuppression exerted by the Gal3BP/Gal3 complex. This led to an increase in IFN-γ and the activation of CD4, CD8 and CD56 effector cells. This study suggests a tumor escape mechanism that may contribute to the development of a different immunotherapy strategy that complements current therapies used for TNBC.